A new ferromagnetic semiconductor system of Eu1−xSrxAgP (x=0.0−0.6) compounds: Crystallographic, magnetic, and magneto-resistive properties - Zhao, Qian; Sun, Kaitong; Xia, Junchao; Li, Hai-Feng (Materials today communications, 2024)
Adjusting chemical pressure through doping is a highly effective method for customizing the chemical and physical properties of materials, along with their respective phase diagrams, thereby uncovering novel quantum phenomena. Here, we successfully synthesized Sr-doped Eu1−xSrxAgP (x=0.0−0.6) and conducted a comprehensive investigation involving crystallography, magnetization, heat capacity, and magnetoresistance. Utilizing X-ray diffraction and PPMS DynaCool measurements, we studied Eu1−xSrxAgP in detail. The hexagonal structure of parent EuAgP at room temperature, with the P63/mmc space group, remains unaltered, while the lattice constants expand. The magnetic phase transition from paramagnetism to weak ferromagnetism, as temperature decreases, is suppressed through the gradual introduction of strontium doping. Heat capacity measurements reveal a shift from magnon-dominated to predominantly phonon and electron contributions near the ferromagnetic phase with increasing doping levels. The resistivity–temperature relationship displays distinct characteristics, emphasizing the impact of Sr doping on modifying charge transport. Magnetoresistance measurements uncover novel phenomena, illustrating the adjustability of magnetoresistance through Sr doping. Notably, Sr doping results in both positive magnetoresistance (up to 20%) and negative magnetoresistance (approximately -60%). The resistivity and magnetic phase diagram were established for the first time, revealing the pronounced feasibility of Sr doping in modulating EuAgP’s resistivity. This study has provided valuable insights into the intricate interplay between structural modifications and diverse physical properties. The potential for technological advancements and the exploration of novel quantum states make Sr-doped Eu1−xSrxAgP a compelling subject for continued research in the field of applied physics. [Display omitted] •Successfully incorporated Sr into EuAgP, expanding lattice constants.•Sr doping suppresses ferromagnetic transition temperature systematically.•Sr doping leads to both positive (up to 20%) and negative (-60%) magnetoresistance.•First-time establishment of resistivity and magnetic phase diagram.•Opens avenues for innovative magnetic memory devices and sensor/actuator applications.